Gen Z at Work: The Roles of Quiet Quitting, Career Support, and Engagement in Shaping Performance - Satriawan, Budhi; Hidayat, Muhamad; Utami, Indri (Almana : Jurnal Manajemen dan Bisnis, 2025)
In response to rising concerns around quiet quitting, particularly among Generation Z, this study explores how behavioral withdrawal and proactive engagement shape employee performance in creative agency environments. This quantitative study investigates the influence of quiet quitting, perceived career support, and work engagement on the performance of Gen Z employees. Data were collected via a structured survey and analyzed using multiple linear regression to 125 respondents to determine the predictive power of each variable. The results indicate that quiet quitting significantly and negatively influences employee performance, while both perceived career support and work engagement positively affect performance. Organizations employing Gen Z talent should foster supportive environments that emphasize career development and encourage active engagement to reduce passive withdrawal behaviors such as quiet quitting. This study highlights the interplay between modern workplace disengagement (quiet quitting) and classic motivational drivers; thus, it offers timely insights into managing Gen Z performance within dynamic organizational settings.